Why Basel II failed and why any Basel III is doomed - Ranjit Lall (University of Oxford, Global Economic Governance Programme (GEG), 2009)
According to conventional wisdom, the Basel II Accord - a set of capital adequacy standards for international banks drawn up by a committee of G-10 supervisors - is essential if we are to avoid another financial crisis. This paper argues that this conclusion is false: Basel II is not the solution to the crisis, but instead an underlying cause of it. I ask why Basel II's creators fell so short of their aim of improving the safety of the international banking system - why Basel II failed. Drawing on recent work on global regulatory capture, I present a theoretical framework which emphasises the importance of timing and sequencing in determining the outcome of rule-making in international finance. This framework helps to explain not only why Basel II failed, but also why the latest raft of proposals to regulate the international banking system - from the US Treasury's recent financial white paper to the latest round of G-20 talks in Pittsburgh - are likely to meet a similar fate.
Keywords: 330; Internationaler Finanzmarkt; Bankgeschäft; Bankenaufsicht; Bankenkrise; Basler Akkord; Welt